δ18O and δ13C of Cibicidoides wuellerstorfi and related species and carbonate chemistry of ambient sea water - Nederbragt, Alexandra J (PANGAEA, 2023)
The δ13C composition of Cibicidoides wuellerstorfi and other Cibicidoides spp is an important tool to reconstruct past changes in the deep ocean carbon cycle. The species are expected to match the δ13C of ambient dissolved inorganic carbon (DIC), although it has been recognised that substantial offsets can occur. I present a compilation of Late Holocene δ13C and δ18O data for named Cibicidoides species in combination with fully resolved carbonate chemistry at each core location, with the aim to test if variation in isotope composition is related to ambient carbonate saturation. Stable isotope data were pre-screened to remove sections with mixed glacial-Holocene Cibicidoides specimens. The resultant database contains δ13C and δ18O data for C. wuellerstorfi from 252 globally distributed core localities and 29 localities for other named Cibicidoides species. Oceanographic data were compiled from published 1° x 1° gridded data sets, including a global reconstruction of pre-industrial δ13C-DIC and δ18O of ocean water. The expected carbonate δ18O was calculated using an empirical temperature equation for inorganic calcite. Concentrations of dissolved carbonate species and saturation state were calculated as a function of depth, salinity, and temperature.
Keywords: Atlantic; carbonate saturation; Cibicidoides spp.; Cibicidoides wuellerstorfi; ẟ13C; ẟ18O; Pacific; Southern Ocean